Performance Talk: Next Generation Management of Organizational Performance - Brian Kane (Copenhagen Business School (CBS), 2010)
Managers must aspire to understand their organization in a way that allows them to take appropriate actions when necessary and to be able to utilize tools which encourage the organization to behave in a desirable way. The field of performance management deals with these objectives and is becoming increasingly pervasive. However, the author's personal experience and substantial scholarship suggest that performance management is linked to dysfunctional behavior in organizations. Various current explanations for the link between measurement and dysfunction revolve around observability or knowledge of the transformation process, but seem simplistic and inadequate. This work examines measurement as one representational form out of many others, for example text. It is proposed that the representational form used in performance management practice is implicated with dysfunctional behavior. This demands an exploration of the relevant facets of organizational reality which influence the relationship with various representational forms. After a theoretical positioning, the relationship is explored empirically through onsite visits at two Microsoft Corporation locations in Copenhagen and Redmond. Thirty stories of performance management, based on interviews with senior managers, are presented. The stories provide the basis for establishing a rich understanding of organizational reality and the implications of using various representational forms in terms of dysfunctional behavior. These implications lead to a fundamental rethinking of the form and boundaries of performance management theory and practice, and emphasize the need for a multi-paradigmatic approach to performance management, which is presented.
hdl:10398/8015
Keywords: 650